Studies on periphyton grazing rate of Labeo calbasu (Hamilton) - Rahman, M M; Haque, M M; Narejo, N T; Islam, S; Rahmatullah, S M (Indian Journal of Fisheries, 2011)
Studies were undertaken to investigate the grazing rate of Labeo calbasu on periphyton for a period of ten months from July 1998 to April 1999. It was observed that periphyton densitysignificantly (p